球類活動對智能障礙學生視覺動作整合的影響 Effects of Ball Activities on Visual-Motor Integration in Students with Intellectual Disabilities - 張芳慈 Fang-Tsyr Chang (National Taiwan Normal University, 2021)
有鑑於智能障礙學生視覺動作整合能力的落後現象足以影響其日常生活與學校學習的活動表現，本研究乃探討職能治療球類活動對智能障礙學生視覺動作整合能力的介入成效。研究採單一受試研究法之跨行為多基線設計，以兩位國小特教班智能障礙學生為研究對象，自變項為職能治療接球、投擲球及滾球訓練活動，依變項則為受試者的視覺動作整合能力，同時配合教師回饋問卷進行社會效度分析。研究結果顯示，職能治療接球、投擲球及滾球訓練活動確實能提升智能障礙學生視覺動作整合能力，且具有立即成效與維持成效。此外，職能治療接球、投擲球及滾球訓練活動的社會效度良好，能使學生在日常生活與學校學習之相關 功能表現上更為進步。 Students with intellectual disabilities often lag behind their peers in terms of visual-motor integration. These limited visual-motor integration abilities reduce their performance in terms of daily living activities and academic learning. The purpose of this study was to determine the effects of ball activities on visual-motor integration in students with intellectual disabilities. A single case study with a multiple-baseline design across various behaviors was adopted. Two students were included in this study. The independent variables were catching, throwing, and rolling ball activities, and the dependent variable was the visual-motor integration ability of the participants. Social validity was also assessed by incorporating teachers' questionnaires into the study. The main findings are as follows: catching, throwing, and rolling ball activities in occupational therapy were helpful for improving participants' visual-motor integration performance and resulted in immediate, maintainable, and satisfactory effects. High social validity was also demonstrated, leading to the conclusion that the intervention can improve students' performance regarding daily living activities and academic learning.